Innovation of clockwise osseodensification technique for primary stability in dental implant: a low-density bone cadaveric study - Rittipakorn, Pawornwan; Ouyyamwongs, Warisara; Boonpitak, Kwanwong (Frontiers in Dental Medicine, 2025)
IntroductionThis cadaveric study evaluated the effect of a novel clockwise osseodensification (OD) technique on primary implant stability in low-density bone.Materials and methodsForty implants were placed in paired sites of nine formalin-fixed human tibiae, comparing OD (n = 20) with standard drilling (SD; n = 20). Primary stability was assessed by maximum insertion torque (IT) and implant stability quotient (ISQ). Postoperative bone-implant interface characteristics were examined using cone-beam computed tomography (CBCT), periapical radiography, and synchrotron-based x-ray tomographic microscopy (SR-µCT).ResultsThe OD group showed higher mean ISQ (67.5 ± 6.5) and IT (34.0 ± 6.6 Ncm) values than the SD group (62.9 ± 9.3; 29.5 ± 7.6 Ncm, respectively), although these differences were not statistically significant (p > 0.05). The results indicate a trend toward improved primary stability with OD (ISQ: p = 0.077; IT: p = 0.052). A statistically significant moderate positive correlation between IT and ISQ was observed in the OD group (ρ = 0.577, p = 0.0077) but not in SD (ρ = 0.208, p = 0.3778), indicating greater predictability of stability outcomes with OD. Radiographic analysis revealed denser peri-implant bone and reduced radiolucency in OD sites, indicating a tendency toward improved bone compaction and closer implant contact. SR-µCT observations qualitatively demonstrated a more condensed trabecular architecture around OD implants compared with SD, consistent with enhanced local bone compaction.DiscussionThese findings indicate that OD produces more consistent stability values and a stronger IT–ISQ relationship than SD, potentially enhancing the reliability of resonance frequency analysis in low-density bone. Unlike conventional counterclockwise OD, Clockwise OD uses densifying burs in the cutting direction at moderate speeds (800 rpm), offering a simpler, less technique-sensitive alternative without sacrificing the benefits of bone condensation. Within the limitations of a cadaveric model, OD demonstrated consistent stability values and a trend toward improved primary mechanical outcomes compared with SD. Further in vivo studies are required to confirm these findings and evaluate long-term biological effects.